Pengaruh Kualitas Pelayanan, Lokasi dan Strategi Promosi Terhadap Minat Beli Konsumen Beras UD Berkah Mandiri - Pratama, Mohammad Riski Eka; Kurniawan, Brahma Wahyu; Rahmawati, Zulfia (Universitas Sains dan Teknologi Komputer, 2025)
This study aims to analyze the influence of service quality, location, and promotional strategies on consumers’ purchasing interest in UD Berkah Mandiri rice. The study employs a quantitative method with a total population of 150 respondents. The sampling technique used in this study is accidental sampling. The sample consisted of 60 respondents, determined using Slovin’s formula. The analytical tool employed in this study is SPSS 25.0. The results indicate that service quality has a significant effect on purchasing interest, that location has a substantial impact on it, and that promotional strategies have a significant effect on it. Furthermore, service quality, location, and promotional strategy simultaneously have a considerable effect on purchasing interest.